Korundna keramika za spajanje s kovino - Šventner-Kosmos, Alenka (Kovine zlitine tehnologije, 1998)
Metal-to-ceramic seals are widely used in high vacuum technology. Dense high alumina ceramics with average grain diameter from 15 to ?$20\mum$? and densities over ?$3.70g/cm^3$? are the most suitable for MoMn metallization. In the present work 98% ?$Al_2O_3$? ceramics with additives from the ?$CaO-SiO_2$? and ?$CaO-Mg-SiO_2$? systems were ivestigated. The influence of sintering conditions, additive composition and starting alumina powder on densification and microstructure development was studied. The most suitable microstructures with average grain diameters of 14 and ?$20\mum$? were achieved with a coarse grained starting alumina powder and additive composition of 35% CaO, 5% MgO, 60% ?$SiO_2$? or 40% CaO and 60% ?$SiO_2$?, with prolonged sinterating at 1700°C.
Keywords: ceramic; keramika; korund; kemijske lastnosti; gostota; mikrostruktura